Development and evaluation of an Internet-based program to improve the mental health and wellbeing of young men. Issue 1 (20th April 2015) - Ellis, Louise A.; McCabe, Kathryn; Davenport, Tracey; Burns, Jane M.; Rahilly, Kitty; Nicholas, Mariesa; Hickie, Ian B
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to describe the development of WorkOut, an Internet-based program designed to help young men overcome the barriers towards help-seeking and to build the skills they need to understand and manage their own mental health. Information and communication technologies (ICT) hold great potential to significantly improve mental health outcomes for hard-to-reach and traditionally underserved groups. Internet-based programs and mobile phone applications may be particularly appealing to young men due to their convenience, accessibility and privacy and they also address the strong desire for independence and autonomy held by most men. Design/methodology/approach – In this paper, we describe the design process itself, and the strategies used for multi-disciplinary collaboration. The initial evaluation process and results are also described which consisted of three distinct phases: website statistics; one-on-one user testing; and pilot interviews. Findings – The results suggest that WorkOut has the potential to attract young men. However, further work is needed to ensure that users remain engaged with the program. Originality/value – The difficulties encountered and lessons learned provide an insight into the factors that should be considered in the design and evaluation of future ICT-based strategies within the mental health domain, as well as their potential applicability to clinical and educational settings.